2009
DOI: 10.1016/j.jss.2008.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Breast Cancer Survival: An Analysis by Age and Stage

Abstract: Background-Black women often present with advanced-stage breast cancer compared with White women, which may result in the observed higher mortality among Black women. Agerelated factors (e.g., comorbidity) also affect mortality. Whether racial disparities in mortality are evident within age and/or stage groups has not been reported, and risk factors for greater mortality among Black women are not well defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 34 publications
4
53
1
Order By: Relevance
“…Our findings are consistent with some[2, 5] though not all[24] studies. In one study[2] of women ≥ 65 years, Black women who had received chemotherapy had no worse mortality than White women, though those that didn’t receive chemotherapy had significantly worse survival.…”
Section: Discussionsupporting
confidence: 94%
“…Our findings are consistent with some[2, 5] though not all[24] studies. In one study[2] of women ≥ 65 years, Black women who had received chemotherapy had no worse mortality than White women, though those that didn’t receive chemotherapy had significantly worse survival.…”
Section: Discussionsupporting
confidence: 94%
“…In our study, the tumors in patients aged 40-44 and 45-49 years had the highest frequencies of ER and PR positivity among the nine age groups examined and a high percentage of grade 1 histology. Even among very young patients, our study showed that patients aged ,35 years had significantly higher frequencies of tumor size #2 In terms of patient outcomes, the relapse risk among patients aged 40-49 years has not been reported to differ significantly from that in patients aged 50-59 years in Western countries [13][14][15][16]. However, in the current study, patients aged 40-44 and 45-49 years had significantly more favorable DFS in univariate analysis compared with patients in the other age groups.…”
Section: Discussionmentioning
confidence: 64%
“…These within-stage disparities have been shown to be independent of other tumor characteristics and more pronounced among later stage tumors and among women younger than 65 years of age. 5,6 Therefore, factors other than tumor characteristics may be influential.…”
Section: Introductionmentioning
confidence: 99%